A case report of CIC–DUX4 fusion-positive sarcoma in the pelvic cavity with targeted next-generation sequencing results - Wu, Qian; He, Ying (Frontiers in Oncology, 2022)
CIC-DUX4 fusion-positive sarcoma is a subtype of undifferentiated small round cell sarcoma which is rarely to be reported. As far as we know, less than 200 cases were reported worldwide to date. The clinicopathologic characteristics of this kind of tumor are nonspecific which makes it difficult to be diagnosed. Therefore, more cases are required to enrich the diagnosis and treatment experience. Here, we present a 17 year-old Asian girl diagnosed as CIC-DUX4 fusion-positive sarcoma after target next generation sequencing. Her clinical manifestation was abdominal pain. Furthermore, a mass in the pelvic cavity and massive ascites were found after imaging examination. The mass was sent to pathology department for definite diagnosis after resection and the micromorphology showed an undifferentiated sarcoma with massive necrosis. The tumor cells were round to spindle with clear to eosinophilic cytoplasm and vesicular nuclei. Rhabdoid cells and myxoid mesenchyme were focally showed. Immunohistochemical staining showed diffusely positive for vimentin, cyclinD1, Fli-1, WT-1 and very focally positive for CD99. Besides, the target next generation sequencing also revealed other genetic changes of this tumor including LongInDel of POLE, copy number variant of CD79, low tumor mutational burden and microsatellite stability. With the follow-up time of 6 months, the patient was survive with disease and received chemotherapy routinely. This report presented a rare primary site CDS and reveal novel genetic changes which enrich the manifestation, histology and cytogenetic scales of this rare sarcoma. In addition, we have summarized the clinicopathologic characteristics of this tumor by reviewing the literature to get a better understanding of CIC-DUX4 fusion-positive sarcomas, which may be helpful for diagnosis and treatment.